(untitled) (International journal of artificial intelligence, 2026)
The article examines individual volitional efforts and the influence of the social environment. It considers the psychological features of developing independent work activities in students, as well as theoretical data on students' self-improvement efforts. The issue of enhancing students' cognitive activity in higher education institutions, taking into account age-related and pedagogical-psychological characteristics is also discussed.